2023
DOI: 10.1007/s11557-023-01892-7
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gap between the number of Phytophthora species isolated through baiting a soil sample and the number revealed through metabarcoding

Abstract: This review assesses possible reasons for the discrepancy between the high numbers of Phytophthora species and putative new species isolated from environmental samples using metabarcoding, compared with the low number cultured and identified through bating. Molecular protocols are unlikely to result in high numbers of false positives, except that variants in young hybrid species may be incorrectly identified as different species. Baiting conditions favour parasitic species that are fast to sporulate, able to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Interestingly, mycorrhizal associations contribute to priming the defences of their hosts by activating the JA‐dependent responses (Pozo & Azcón‐Aguilar, 2007). Most species of Phytophthora are haemibiotrophs with a variable biotrophy period before switching to necrotrophy (Sarker et al ., 2023). The JA pathway is commonly induced in response to necrotrophic pathogens (Glazebrook, 2005), as observed in roots of E. todtiana here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, mycorrhizal associations contribute to priming the defences of their hosts by activating the JA‐dependent responses (Pozo & Azcón‐Aguilar, 2007). Most species of Phytophthora are haemibiotrophs with a variable biotrophy period before switching to necrotrophy (Sarker et al ., 2023). The JA pathway is commonly induced in response to necrotrophic pathogens (Glazebrook, 2005), as observed in roots of E. todtiana here.…”
Section: Discussionmentioning
confidence: 99%
“…Introduced pathogens pose a significant threat to plant productivity and diversity – exemplified by the devastating impact of root‐rot Phytophthora cinnamomi in highly diverse ecosystems (Lambers et al ., 2013; Hardham & Blackman, 2018) – but plants have also co‐evolved with soil‐borne pathogens, including native oomycete species of the Phytophthora genus (Ricklefs, 2010; Rea et al ., 2011; Albornoz et al ., 2017; Sarker et al ., 2023). Previous studies have demonstrated the enhanced resistance of both AM‐ and ECM‐colonised plants to Phytophthora spp.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact metabarcoding showed that P. cinnamomi was more common in orchards than natural vegetation, isolation rates did not re ect this. The difference in number of species detected through direct isolation (by soil/root baiting) versus metabarcoding has long been debated (Sarker et al 2023a). It is thought that in soil/root baiting, the isolation outcomes depend on Phytophthora propagules in the analysed samples since the method relies on motile zoospores released from the sporangia being attracted to a live bait (Sarker et al 2021).…”
Section: Comparison Of Metabarcoding Molecular Detection Methods and ...mentioning
confidence: 99%
“…It is thought that in soil/root baiting, the isolation outcomes depend on Phytophthora propagules in the analysed samples since the method relies on motile zoospores released from the sporangia being attracted to a live bait (Sarker et al 2021). Baiting conditions favours fast-sporulating species, able to infect a range of bait species, achieve infection with a low number of zoospores, and fast-growing on selective agar (Sarker et al 2023a). For this reason, baiting success depends upon the species present and the propagule viability when the sample was collected (Sarker et al 2021;Sarker et al 2023b).…”
Section: Comparison Of Metabarcoding Molecular Detection Methods and ...mentioning
confidence: 99%
“…Green et al (2020) effectively deployed a mix of different fresh leaf species as baits in a study investigating the range of Phytophthora species present in public parks, whilst in comparative trials in Australia, primarily looking at soils, a multiple bait system used by the Centre for Phytophthora Science and Management was the most effective baiting procedure (Burgess et al, 2021). The age, quality, and physiological state of the plant tissues being used as baits are hugely influential on the results obtained (Themann et al, 2002;Hüberli et al, 2013;Werres et al, 2014), and inclusion of dead tissues within a bait mix can increase the number of species captured (Wielgoss et al, 2009;Aram and Rizzo, 2018;Sarker et al, 2023a). When baiting is deployed in comparative experiments over time, variability can be reduced by using more controllable tissues such as seedlings or seedling parts (Banihashemi and Mitchell, 1975;Erwin and Ribeiro, 1996;Pettitt et al, 1998).…”
Section: Baitingmentioning
confidence: 99%